The Direct Impact Effect of Different Foot Orthotic Designs on the Plantar Loading of Patients with Structural Hallux Limitus: A Quasi-Experimental Study - Magdalena Martinez-Rico; Gabriel Gijon-Nogueron; Ana Belen Ortega-Avila; Luis Enrique Roche-Seruendo; Ana Climent-Pedrosa; Enrique Sanchis-Sales; Kevin Deschamps (Applied Sciences, 2024)
Background: This study examines the effect of two types of custom-made foot orthoses (CFOs) in patients with structural hallux limitus (SHL). Methods: In this quasi-experimental, repeated measures study, 24 participants with SHL were sampled. Two CFOs—cut-out CFO and anterior stabilizer element (AFSE) CFO—were compared using minimalist SAGURO neoprene shoes: no foot orthoses (FO), cut-out CFO, and AFSE CFO. Plantar pressures and center of pressure (CoP) displacement were measured using a Podoprint® platform. Results: Both CFOs shifted the CoP medially during midstance (p < 0.001 with AFSE CFO and p = 0.0036 with cut-out CFO). The AFSE CFO showed a more anterior CoP in midstance, while the cut-out CFO affected anterior CoP in midstance and pre-swing. The AFSE CFO significantly increased pressure in the second toe, lesser metatarsal heads (MTH), midfoot, and rearfoot. In contrast, the cut-out CFO decreased pressure in the second MTH and lesser toe regions, increasing pressure in the midfoot and heel. Both CFOs lowered the hallux/first MTH ratio compared to shod without CFO. Conclusions: The cut-out CFO led to medial and anterior CoP displacement, reducing lateral foot and hallux pressure while transferring loads to the first MTH. The AFSE CFO caused a similar shift by increasing loads on the first MTH.